Effect of oxydesulphurization on the combustion characteristics of coal - Yaman, Serdar; Kücükbayrak, Sadriye; Yaman, Serdar (Elsevier BV, 1997)
Abstract Desulphurization of a Turkish lignite by oxydesulphurization using dilute alkaline solutions, obtained by the extraction of fly ash with water, was carried out under 0–1.5 MPa partial pressure of oxygen at temperatures between 403 and 498 K for 30–90 min time intervals. TGA was performed to compare the combustion characteristics of original and desulphurized lignite samples. DTG curves were derived and the effects of desulphurization conditions such as temperature, partial pressure of oxygen and time on coal reactivity were studied considering ignition temperature, maximum combustion rate, combustion period, and the end temperature of combustion. Relations between coal reactivity and removals of sulphur and ash contents were also studied.